Accounting for privatization and sustainable development in Pakistan - Zeeshan Mahmood; Rehana Kouser; Zubair Ahmad; Waris Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
This paper analyzes the post-privatization performance and organizational changes of a Pakistani State Owned Enterprise (SOE). Drawing on the concept of sustainable development, this study examines the performance of the firm from three perspectives - economic, social and environmental. The analysis is based on data gathered from annual reports, public documents and semi-structured interviews with key personnel. This study reveals substantial improvement in company profitability. However instead of increase in operational efficiency, the main reason for improved profitability is increase in sale prices and decrease in employee related cost which has negative social implications. Environmental performance of the company has improved mainly in those areas where there is a case for increase in economic performance. The case study concludes that the main focus of the new management was on economic performance rather than concerns for sustainable development. Various organizational changes were made after privatization to ensure quick decision making on various proposals that enhances shareholder value in the company.
Keywords: 330; privatization; sustainable development; performance evaluation; state owned enterprises; Pakistan